PERSEPSI MAHASISWA KEPERAWATAN TENTANG PERAWATAN SPIRITUAL (SPIRITUAL CARE) - Azzahra, Meza Belindiani; Nur'aeni, Aan; Kosasih, Cecep Eli (STIKes Maharani Malang, 2018)
Perception that received by nursing student can determine their behavior toward spiritual care in nursing practice. It is important to be identified in the academic stage to evaluate whether the learning process is able to support student perception. The purpose of this study was to identify the perception of nursing students about spiritual care. This research was quantitative descriptive. Population were final year and third year nursing student at one of the institution in West Java. Samples were acquired using a proportionate stratified random sampling technique (n=171). Data were collected using a spiritual care giving scale (SCGS). Data were analyzed using frequency distribution, percentage, and mean. Result of this research indicated that all of respondents had a favorable perception about spiritual care. However, there still aspects that had lower mean value comparing other aspects. Based on frequency distribution, there were number respondents who had disagree statement about form of spiritual care (11,1%) and individual’s integrity when having spirituality in theirself (12,3%). The conclusion of this research was all respondents had a favorable perception of spiritual care. Nevertheless, there were aspects that need to be improved, such as spiritual care attitudes and definition of spiritual care. These can be improved through a specific education regarding spirituality and spiritual care.